2012
DOI: 10.1016/j.molcel.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Direct Regulation of GTP Homeostasis by (p)ppGpp: A Critical Component of Viability and Stress Resistance

Abstract: Summary Cells constantly adjust their metabolism in response to environmental conditions, yet major mechanisms underlying survival remain poorly understood. We discover a post-transcriptional mechanism that integrates starvation response with GTP homeostasis to allow survival, enacted by the nucleotide (p)ppGpp, a key player in bacterial stress response and persistence. We reveal that (p)ppGpp activates global metabolic changes upon starvation, allowing survival by regulating GTP. Combining metabolomics with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
457
3
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(495 citation statements)
references
References 43 publications
25
457
3
10
Order By: Relevance
“…This idea also is supported by the observation that the stringent response seems to be linked to the cellular energy state, because decreased GTP levels render B. subtilis more capable of surviving amino acid starvation, albeit at lower growth rates (35,36). Both events are closely connected to ppGpp and pppGpp, which also inhibit multiple enzymes for GTP biosynthesis (35,37,38). Furthermore, these data strongly indicate that pppGpp and ppGpp execute different biological functions.…”
Section: Discussionmentioning
confidence: 75%
“…This idea also is supported by the observation that the stringent response seems to be linked to the cellular energy state, because decreased GTP levels render B. subtilis more capable of surviving amino acid starvation, albeit at lower growth rates (35,36). Both events are closely connected to ppGpp and pppGpp, which also inhibit multiple enzymes for GTP biosynthesis (35,37,38). Furthermore, these data strongly indicate that pppGpp and ppGpp execute different biological functions.…”
Section: Discussionmentioning
confidence: 75%
“…Gmk is the enzyme responsible for the conversion of GMP to GDP during de novo synthesis of GTP, whereas HprT is involved in the salvage pathway, converting both hypoxanthine to IMP and guanine to GMP. The activities of these enzymes from both B. subtilis and E. faecalis, as well as Gmk from S. aureus (Gmk SA ), have been shown to be inhibited in the presence of (p)ppGpp, thus lowering intracellular GTP levels to a range that supports survival during starvation (28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether (p)ppGpp can directly inhibit the function of the staphylococcal HprT enzyme, and to confirm that Gmk SA can be inhibited, the enzymatic activities of both proteins were monitored in the presence of both ppGpp and pppGpp. Enzymatic assays monitoring the conversion of guanine to GMP by HprT or GMP to GDP by Gmk were set up as previously described (28). This analysis revealed that the HprT and Gmk enzymes from S. aureus are inhibited by both ppGpp and pppGpp ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations